Estudo do remodelamento do proteoma cardíaco após a indução de hipertrofia por isoproterenol em camundongos - Ricardo Cambraia Parreira (2018)
Cardiac hypertrophy is a pathological enlargement of heart muscle resulting from increased cardiomyocytes in size and changes in extracellular matrix. Proteome studies of the cardiovascular diseases have demonstrated altered expression of proteins related to energy metabolism, heat shock proteins, redox system, calcium and cytoskeleton signaling. Nevertheless, the interaction between proteins and key regulators underlying cardiac remodeling are still elusive. To gain a better understanding on hypertrophy, we performed a qualitative proteomic study of heart extracellular matrix after a decellularization process and a quantitative (label-free) cardiomyocytes proteomic analysis in the isoproterenol-induced cardiac hypertrophy model. Altogether, our proteomic data has shown that the treatment induced changes in biochemical pathways and cell signaling. We also highlighted proteins and gene expression regulators potentially involved in the observed proteome remodeling. This work provides a better understanding about the modulation of isoproterenol-induced cardiac hypertrophy model.